Persepsi Mahasiswa IPB University terhadap Personal Branding Jerome Polin pada Platform TikTok - Nadia Fitri Mahani; Amiruddin Saleh; Harvia Atika Zahira (Educatoria : Jurnal Ilmiah Ilmu Pendidikan, 2026)
This study aims to analyze the perceptions of IPB University students towards the personal branding of educational figures on TikTok with a case study of Jerome Polin. The study uses a descriptive qualitative approach through in-depth interviews with three active IPB University students from different study programs, who actively use TikTok and follow the content of @jeromepolin98. Informants were selected purposively based on their experience in accessing and observing Jerome Polin's educational content. The number of informants was limited because the study focused on exploring experiences and perceptions in depth, so the findings are not intended to be generalized to all IPB University students. The results show that the informants' positive perceptions of Jerome Polin's personal branding are mainly formed through the consistency of specialization, differentiation, and digital identity displayed in the content. Informants perceive Jerome as an educational figure who is skilled, communicative, authentic, and trustworthy, which is related to his academic background in Japan and the consistency of delivering educational messages. The short video format, use of light language, and the combination of educational and entertainment elements are perceived to help make the message more interesting and easily accepted. The novelty of this research lies in understanding how students interpret the personal branding of educational figures through a combination of credibility, differentiation, and an edutainment approach in the context of TikTok. This study concludes that digital identity consistency, credibility, and the presentation of edutainment content are perceived to support the acceptance of Jerome Polin as an educational figure on TikTok.